Sustainable develoment of Ostrov area, Constanta county through rural and wine tourism - Radu Andrei Iova; Elena Lascăr (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The purpose of this paper is to discuss the conceptual and solid dimension of the sustainable development of Ostrov area, Constanta county, regarding the rural and wine tourism and wine, and their correlation and determination of the relationship between them. The research is both a theoretical one, which exposes the ideas on this aspect, but also a practical one, which can show the efficiency and sustainability of applying a development plan. The ultimate purpose is to provide a theoretical and methodological, but also an applicative background for the development of Ostrov area. The suggested aspects have a relevant importance for development, because it determines the areas that are attractive and repulsive, managing to highlight proposals for the development strategy of the area. This approach is based on the use of some qualitative data, analyzing and forecasting the dynamics of the commune and area, and the tourism potential generating image, and finally ideas to improve and promote the existing situation through an integrative management. The main theme of this paper is to highlight and capitalize the importance of Ostrov area, for which, through the rural and wine tourism, the sustainable development becomes a certainty.
Keywords: 330; development potential; sustainable tourism; rural tourism; wine tourism; wine tasting tourism